Peculiarities of Kazakh reality translation with cultural-historical educational components - Yerbulatova, I. K.; Gilazetdinova, G. K.; Bozbayeva, A. G. (International Journal of Higher Education. - 2019, 2019)
The development of intercultural relations and the globalization of multicultural civilization gives rise to the need for educational study the elements found in the language of each nation, not only in the national-cultural aspect but also in comparative translation. At the present stage of translation educational study development, special attention is paid to the issues of the national and historical specifics of the original work preservation and transmission in the process of translation into the language of another culture. This article discusses the linguistic realities and their role in the national and historical identity reflection of a different culture, presented in the context of a work of art. As the result of the study, the methods of Kazakh historical reality transmission are analyzed, and the specifics of their translation into Russian is described on the basis of the works of Kazakh writer Dukenbai Doszhan (XX century). The article highlights the sign of the “dual nature” of historical realities in archaized texts of fiction, on which the choice of a translation solution depends. The main results and conclusions of the study presented in this article show that the distance in time and space separating the source text from the text of translation inevitably leads to national-cultural biases, which should be taken into account during a text translation that must be adequate to the original text.Развитие межкультурных отношений и глобализация мультикультурной цивилизации порождает потребность в образовательном изучении элементов языка каждой нации не только в национально-культурном аспекте, но и в сравнительном переводе. На современном этапе развития переводческой педагогики особое внимание уделяется вопросам национально-исторической специфики сохранения и передачи оригинального произведения в процессе перевода на язык другой культуры. В данной статье рассматриваются языковые реалии и их роль в отражении национальной и исторической идентичности другой культуры, представленной в контексте произведения искусства. В результате исследования на основе произведений казахского писателя Дукенбая Досжана (ХХ век) проанализированы способы передачи казахской исторической реальности и описана специфика их перевода на русский язык. В статье подчеркивается признак «двойственности» исторических реалий в архаизированных текстах художественной литературы, от которого зависит выбор переводческого решения. Основные результаты и выводы исследования, представленные в этой статье, показывают, что расстояние во времени и пространстве, отделяющее исходный текст от текста перевода, неизбежно приводит к национально-культурным предубеждениям, которые следует учитывать при переводе текста, который необходимо адекватно исходному тексту.
Keywords: импакт-фактор 2019; научный журнал; периодическое издание; скопус; языкознание; зарубежное издание; дальнее зарубежье; казахский язык; зарубежные авторы